Optimum placement of distributed generation and parking lots for loss reduction in distribution networks - Moradijoz, Mahnaz; Ghazanfarimeymand, Azam; Moghaddam, Mohsen Parsa; Haghifam, Mahmud Reza (2012 Proceedings of 17th Conference on Electrical Power Distribution Networks, 2012)
Optimal placement of distributed generation (DG) units and proper allocation of parking lots, providing vehicle-to-grid (V2G) power, in order to reduce loss in distribution networks is studied in this paper. The objective function containing active and reactive power indices is minimized using genetic algorithm. Power flow is done utilizing backward-forward sweep method. Finally, simulation is carried out on a 30 bus test system. Placement of DGs and parking lots are done simultaneously in the test system. Results show a significant reduction of losses with presence of DG units and parking lots. Also, the effect of variation both in number of vehicles in parking lot and the battery charge rate on the results is investigated. Simulation results demonstrate that any change in charging rate and the number of vehicles in parking lot lead to variation in the optimum location for parking lot and DG.